2020
DOI: 10.1093/plcell/koaa037
|View full text |Cite
|
Sign up to set email alerts
|

Natural allelic variation in a modulator of auxin homeostasis improves grain yield and nitrogen use efficiency in rice

Abstract: The external application of nitrogen (N) fertilizers is an important practice for increasing crop production. However, the excessive use of fertilizers significantly increases production costs and causes environmental problems, making the improvement of crop N-use efficiency (NUE) crucial for sustainable agriculture in the future. Here we show that the rice (Oryza sativa) NUE quantitative trait locus DULL NITROGEN RESPONSE1 (qDNR1), which is involved in auxin homeostasis, reflects the differences in nitrate (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 68 publications
0
42
0
Order By: Relevance
“…Numerous studies have supported the idea that N regulation is involved in plant development (Zhang S. et al, 2020;. Based on the previously reported genes and published studies, we conducted candidate gene identification.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have supported the idea that N regulation is involved in plant development (Zhang S. et al, 2020;. Based on the previously reported genes and published studies, we conducted candidate gene identification.…”
Section: Discussionmentioning
confidence: 99%
“…Some specialized carriers mediate the auxin's polar transport: incoming carrier proteins of the family AUX1/LAX and outgoing carrier protein of the PIN family. Researchers have proven that the auxin influx carriers (AUX/LAX family) facilitate the uptake of the natural auxin IAA and the synthetic auxin 2,4-dichlorophenoxyacetic acid (2,4-D), but not the synthetic auxin NAA [45][46][47][48][49][50]. The transport specificities and locations of AUX/LAX family members may contribute to the differences in auxin response.…”
Section: Discussionmentioning
confidence: 99%
“…According to Dos Santos et al [75], plant responses to nitrogen supply are dependent on auxin signaling, which can be coming from endogenous biosynthesis or exogenous sources. Zhang et al [49] have shown that, on rice (Oryza sativa), the NUE quantitative trait locus is involved in auxin homeostasis. The promotion of auxin biosynthesis results in improved NUE.…”
Section: Discussionmentioning
confidence: 99%
“…The application of ZNC with controlled-release urea has significantly increased the soil nitrogen supply in the critical period of wheat growth and development ( Qin et al, 2018 ). A recent study demonstrates DULL NITROGEN RESPONSE1 ( DNR1 ) regulates nitrogen metabolism by mediating auxin homeostasis, and OsARFs promotes nitrogen absorption rate by activating the expression of NO 3− metabolic related genes ( Zhang et al, 2021 ). Combined with our research, ZNC promoted the absorption of nitrogen in potatoes, suggesting that ZNC also improves fertilizer utilization efficiency by increasing the absorption of nitrogen in plants ( Figure 2F ), which is beneficial for decreasing fertilizer use and reducing costs in agricultural production.…”
Section: Discussionmentioning
confidence: 99%